3 Methods and Materials Applied in Electrosynthesis - Enders,P.; Francke,R. (Electrochemistry in Organic Synthesis, 2022)
This chapter is intended as a tutorial for the organic chemist and to serve as an introductory guide to the technical and methodological aspects of electrosynthesis. The most important reaction parameters, methods, and materials are covered both from a practical point of view and in their physicochemical context
Keywords: Referencework; organic electrochemistry; electrosynthesis; reaction control; electrochemical cells; supporting electrolytes; electrodes; separators; electrocatalysts; mediators; paired electrolysis; reproducibility